Microbial contamination associated with the processing of tchachanga, a roasted meat product - ANIHOUVI, D.G.H.; KAYODE, Adéchola P. P.; ANIHOUVI, V.B.; AZOKPOTA, PAULIN; KOTCHONI, S.O.; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2013)
This study aimed to assess the microbiological contamination and quality of tchachanga, a roasted meat braised product processed at traditional scale in Benin, West Africa. A survey was performed to collect samples of tchachanga and data related to hygienic conditions of the roasted meat processing environment. A total of 60 samples of tchachanga including skewers, roasted meat and seasoned wrapped meat were collected from different processing sites in Cotonou, Benin. The main food borne microorganisms involved were investigated using standard methods. Moreover, a follow-up of tchachanga processing was performed to identify contamination factors of the product. In this respect, samples were collected at certain steps during the processing, and various microorganisms such as coliforms, pathogenic Staphylococcus and Salmonella were traced. The number of mesophilic aerobic bacteria in different products ranged between 6.47±0.61 and 6.93±0.43 Log (cfu/g). Total coliforms, faecal coliforms and Staphylococci ranged from 1.59 to 4.79, 1.00 to 3.2 and 3.49 to 5.2 Log (cfu/g), respectively. No significant differences were observed in the microbial count of different types of tchachanga investigated, but different processing methods had significant changes in the microbial content of the samples as a result of the processing environments and the ingredients used. The presence of Salmonella sp. was observed in all products.
Keywords: Street food; Tchachanga; meat; microbiology; quality